Isothermal double-cycle catalytic system using DNAzyme and RNase H for the highly selective one-pot detection of oligonucleotides. Issue 8 (14th March 2019) - An, Ran; Kawai, Hayato; Asanuma, Hiroyuki; Komiyama, Makoto; Liang, Xingguo
Abstract : With the use of a double-cycle system involving two catalytic reactions by RNase H and DNAzyme, the signal of oligoDNAs has been specifically amplified in an isothermal mode. Abstract : With the use of a double-cycle system involving two catalytic reactions by RNase H and DNAzyme, the signal of oligoDNAs has been specifically amplified in an isothermal mode. The precursor of DNAzyme was introduced to the system as a ring-structured and inactivated form, which involves the 6-nt RNA portion being complementary to target oligoDNA. In the presence of target oligoDNA, the RNA portion forms a DNA/RNA hetero-duplex and is cut by RNase H. This scission converts the precursor to catalytically active DNAzyme, which in turn disconnects the molecular beacon to produce the amplified signal. Because the covalent bonds were disconnected to provide discrete structural changes in both cycles, high sensitivity and specificity are obtained, indicating the strong potential of this double catalytic cycle method for versatile applications.